PEMBERDAYAAN MASYARAKAT MISKIN MELALUI PROGRAM KELOMPOK USAHA BERSAMA (KUBE) DI KECAMATAN PEMANGKAT PERSPEKTIF EKONOMI SYARIAH - Yuniartik Yuniartik; Munadi Munadi; Alkadri Alkadri (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2020)
The emergence of the idea of ​​empowering the poor through the Joint Business Group program is based on the idea that everyone has the potential and abilities that can be developed. However, the awareness and participation of members of the Joint Business Group on the success of the program is very low. Islam calls for social change to eradicate injustice and improve social welfare. The focus of this research is: 1) How to Empower the Poor through the Joint Business Group Program in Pemangkat District? 2) How is the Empowerment of the Poor through the Joint Business Group Program in Pemangkat Subdistrict with the Islamic Economic Perspective? This study uses a field approach (field research) with a type of qualitative research. The technique of collecting data by means of interviews, observation and documentation. Data analysis used data reduction, data display, conclusion and verification. Primary data sources were obtained from the Social, Community and Village Empowerment Office of Sambas Regency, a companion to the Pemangkat District Joint Business Group, Chair of the Joint Business Group and members of the Joint Business Group. Meanwhile, secondary data is obtained from books on empowerment, previous research that discusses the empowerment of Joint Business Groups and data from the internet. The results showed that empowerment of the poor through programs that have been issued by the government, which can be concluded in this study that the empowerment of the poor through the Joint Business Group program that has been issued by the government is still not in accordance with government expectations due to several factors including location selection, socialization of empowerment. community, the community empowerment process, community independence as an instrument for empowering joint business groups have not been maximally implemented in the field. In addition, the failure to empower the poor through the KUBE program in Pemangkat District is caused by internal and external factors of KUBE that have not implemented sharia economic values in carrying out their business activities, namely lack of fairness, lack of cooperation and lack of trust.